(untitled) (LACCEI, 2024)
A reliable evaluation system must be a guarantee to obtain a qualification that reflects the degree of acquisition of competence. The evaluation must be homogeneous so that teachers assign grades closer to the degree of competence formation in engineering training programs and serve as a reference for more objective feedback. For this reason, this article shows a quantitative method of Measurement System Analysis (MSA) to determine the reliability of the system evaluation and to generate a diagnosis that allows the establishment of adequate strategies to improve the evaluation practice of participating university professors within engineering training in Mexico.